Pseudo-Volkmann Contracture: A Case Report and Review of the Current Literature. (November 2018) - Geissler, Jacqueline; Westberg, Jerald; Stevanovic, Milan
Abstract : Background: Unlike the usual Volkmann contracture as a complication of pediatric forearm fracture, pseudo-Volkmann contracture is not a sequela of ischemia, but rather of a mechanical entrapment of the flexor myotendinous units in the fracture or adhesions. Methods: PubMed search of the English literature was performed using the terminology entrapment and fracture and pseudo-Volkmann. Results: Thirteen articles were identified that described cases of pseudo-Volkmann contracture in pediatric both-bone forearm fractures. Totally, 26 cases were reported in the English literature. Additionally, we describe two more cases in detail. Discussion: Pseudo-Volkmann contracture is well described but uncommon. It most commonly involves the ring finger flexor digitorum superficialis but can occur in all fingers. This entrapment can be identified acutely with intentional examination by confirming full passive motion of the fingers after preferred treatment of both-bone forearm fractures in the pediatric patient. When contracture is identified on examination, surgical intervention to clear the entrapment from the fracture is effective and produces excellent results.